Real-Time Data Transmission and Visualization as a Powerful Technology to Reduce Non-Productive Time During Drilling Operations: Present Day Capabilities, Limitation, and Future Development - Yustian Ekky Rahanjani; Budhi Nugraha (Testing Center for Oil and Gas LEMIGAS, 2020)
This paper primarily is focusing on presenting the non-productive time overview and any kind of non-productive time that can be reduced by real-time data technology, real-time data transmission and visualization infrastructure which supports the processes of aggregation, transmission, and visualization; the example of multipurpose implementation and further innovation and improvements that can be made within the real-time data transmission and visualization, such as real-time reservoir footage calculation during geosteering and drill-time calculation to pick the formation tops and casing point; the challenges and limitation while using real-time data, such as VSAT and local network connectivity issue; and future target and improvement of real-time data usage especially to make an artifi cial intelligence system to predict the potential feature, such as formation or drilling problem while drilling. All of those stuff s could be found by literature study and direct professional experience while handling real-time data system. This technology will inspire the user to design their own solution for their operations. Despite the signifi cant advances on real-time data transmission and visualization, there is signifi cant room to fully use itspotential for advanced workfl ows and the usage of real-time data technology which was proven to reduce the Non-Productive Time that could save the operational cost. We believe that the utilization of real-time data transmission and visualization will defi nitely increase the effi ciency of the drilling operations, especially for multiple wells operations.